Distributed leadership in a low - carbon city agenda - Mohamed, Azalia; Zaiton Ibrahim, Zelina; Silong, Abu Daud; Abdullah, Ramdzani (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
This paper uses Spillane’s (2001) theory and Gronn’s (2000) concerted efforts approach to examine distributed leadership in a low-carbon city agenda. The main purpose of the paper is to find empirical evidence of a relationship between distributed leadership and the achievement of the agenda. Eight constructs emerged that informed our understanding of distributed leadership dimensions within the low-carbon city framework: vision, organizational framework, organizational culture, consensus, instructional programs, expertise, team leader leadership, and team member leadership. The evidence shows that there is a positive relationship between distributed leadership and the outcome of the low-carbon city agenda, and that a dispersed pattern in distributing leadership is required to enhance community engagement. The findings also suggest that an organizational culture that facilitates multiple sources of leadership may largely contribute to the effectiveness of distributed leadership practices in realizing the low-carbon city agenda.